2020
DOI: 10.17275/per.20.4.7.1
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role Of Self-Efficacy In The Relationship Between Problem Solving And Hope

Abstract: The current study aims to investigate the relationship among problem solving, hope, and self-efficacy and to test a model for determining the role of self-efficacy in the relationship between problem solving and hope. It adopted convenience sampling and consisted of 494 undergraduate students (369 females; 125 males). The Hope Scale, General Self-Efficacy Scale and Problem Solving Inventory were applied in order to collect the data. Pearson correlation analysis and two-step Structural Equation Modelling were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Students lacking adequate affective skills might perceive an inability to solve mathematical problems (Öztürk et al, 2020). This study's findings align with prior research indicating a strong relationship between problem-solving skills and other affective abilities, such as self-efficacy, mathematics attitude, mathematics anxiety, and beliefs (Evans et al, 2021;Hoffman, 2010;Hunt et al, 2012;Çam et al, 2020;Demirel et al, 2015;Marchiş, 2013;Hidayat & Ayudia, 2019;Irfan, 2017;Jiang et al, 2021;Nasrullah et al, 2019;Ozturk & Guven, 2016;Soesanto & Dirgantoro, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Students lacking adequate affective skills might perceive an inability to solve mathematical problems (Öztürk et al, 2020). This study's findings align with prior research indicating a strong relationship between problem-solving skills and other affective abilities, such as self-efficacy, mathematics attitude, mathematics anxiety, and beliefs (Evans et al, 2021;Hoffman, 2010;Hunt et al, 2012;Çam et al, 2020;Demirel et al, 2015;Marchiş, 2013;Hidayat & Ayudia, 2019;Irfan, 2017;Jiang et al, 2021;Nasrullah et al, 2019;Ozturk & Guven, 2016;Soesanto & Dirgantoro, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Subsequently, deficiencies in affective skills can intertwine with cognitive skills such as reading comprehension, thereby affecting students' problem-solving prowess (Öztürk et al, 2020). Several studies have explored the association between problem-solving abilities and affective aspects encompassing self-efficacy (Evans et al, 2021;Hoffman, 2010;Hunt et al, 2012;Çam et al, 2020), mathematics attitude (Demirel et al, 2015;Marchiş, 2013;Öztürk et al, 2020), mathematics anxiety (Grežo & Sarmány-Schuller, 2018;Irfan, 2017;Jiang et al, 2021;Karasel et al, 2010;Lai et al, 2015), and beliefs (Kurniawati et al, 2022;Nasrullah et al, 2019;Ozturk & Guven, 2016;Soesanto & Dirgantoro, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy is a key factor in social cognitive theory [ 51 ] and is defined as individuals’ belief in their ability to establish motivational, cognitive, and behavioral resources to complete situational demands. Self-efficacy directly or indirectly affects the behaviors of people, their level of endurance against worries and failures, and the stress they face while dealing with environmental difficulties [ 52 ]. Evidence has shown that people who have high levels of self-efficacy have to control their thoughts and show more stability, and self-efficacy could offer psychological resilience in achieving goals [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca alanyazında bilişsel esnekliğin, problem ve durumlar karşısında alternatif çözümler üretmek, zorluklarla mücadele etmek gibi kavramlarla ifade edildiği görülmektedir (Martin & Rubin, 1995;Martin & Anderson, 1998;Sapmaz & Tayfun, 2013;Dennis & Vander Wal, 2010). Bu doğrultuda alanyazın incelendiğinde ise öz-yeterlik ile problem çözme becerileri arasında pozitif yönde anlamlı düzeyde bir ilişkinin olduğu belirlenmiştir (Yenice, 2012;Çam, Ekşisu, Kardaş, Saatçioğlu & Gelibolu, 2020 (Sagone & De Caroli, 2016;Can & Cantez, 2017, Kılıç, Mammadov, Koçhan & Aypay, 2020. Bu çalışma sonucunu doğrudan destekleyen araştırmaların yanı sıra bireylerin psikolojik sağlamlık düzeylerinin yüksek olmasının onların yaşamı üzerinde olumlu bir etki oluşturduğuna dair araştırma sonuçlarına da rastlanmıştır (Tagay, Karatas, Bayar & Savi-Cakar, 2016;Novotny & Kremenkova, 2016;Balgiu, 2017;Ergün-Başak & Can, 2018).…”
Section: Sonuçunclassified